Conceptualizing the Multilayer Geolinguistic Mapping Framework (MGMF) for Digital Linguistic Atlas Development - Juwintan Juwintan (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
The increasing use of Geographic Information Systems (GIS) has significantly advanced geolinguistic research, particularly in the development of digital linguistic atlases. However, existing studies primarily employ GIS as a visualization tool, while the methodological workflow for transforming linguistic data into spatial information remains insufficiently documented. This study addresses this gap by conceptualizing the Multilayer Geolinguistic Mapping Framework (MGMF), a documented and replicable methodological framework for GIS-based geolinguistic research. An Explanatory Sequential Mixed Methods design was employed using geolinguistic data from Javanese (Cirebon dialect), comprising 267 observation villages, 534 informants, and 200 Swadesh basic vocabulary items. The existing research workflow was analysed and reconstructed into a methodological framework that integrates linguistic processing with spatial analysis in QGIS. The results show that the MGMF comprises five interconnected methodological components that collectively transform linguistic data into spatial information for the development of digital linguistic atlases. Rather than functioning solely as a mapping procedure, the framework documents the logical relationships among successive analytical stages through an input–process–output mechanism, providing a systematic and transparent workflow for GIS-based geolinguistic research. The principal contribution of this study is the conceptualization of a documented, replicable methodological framework that extends the role of GIS beyond spatial visualization to support the systematic transformation of linguistic data into spatial information. By establishing a structured methodological workflow, the MGMF contributes toward the methodological standardization of GIS-based geolinguistic research and provides a reference framework for the development of digital linguistic atlases across diverse regional languages and geographical contexts. A limitation of this study is that the framework was conceptualized from a single case study, namely the Javanese (Cirebon dialect), and therefore requires further empirical validation across other regional languages and geographical settings to confirm its broader applicability.